Self-care education based on local wisdom to improve glycemic control and self-efficacy in type 2 diabetes - Yasa, I Dewa Putu Gede Putra; Surasta, I Wayan; Rasdini, Iga Ari; Iblasi, Abdulkareem S.; Polsook, Rapin; Juanamasta, I Gede (Faculty of Nursing Universitas Padjadjaran, 2025)
Introduction: Effective management of type 2 diabetes mellitus (T2DM) requires structured self-care education supported by family and cultural context. In Bali, health-related decisions are often influenced by patrilineal households where male family members act as primary decision-makers. This study evaluated a self-care education program based on Balinese local wisdom to improve glycemic control and self-efficacy among T2DM patients. Methods: A quasi-experimental design with pre- and post-tests and a control group was conducted at Community Health Center in Bali, Indonesia from June to September 2024. .Seventy patients with T2DM living in patrilineal households were purposively recruited and randomly allocated into intervention (n=35) and control (n=35) groups.. The intervention consisted of twelve weekly sessions of culturally tailored self-care education covering diet, physical activity, monitoring, medication, and foot care, with active involvement of male household decision-makers. Outcome measures included self-efficacy (Diabetes Management Self-Efficacy Scale), HbA1C, and systolic/diastolic blood pressure, analyzed using t-tests. Results: After 12 weeks, the intervention group demonstrated significant improvements compared to controls: self-efficacy (mean difference: 8.37, p<0.001), systolic blood pressure (-4.51 mmHg, p<0.001), diastolic blood pressure (-2.74 mmHg, p<0.001), and HbA1C (-0.61%, p<0.001). Although the HbA1C reduction was modest, it indicates a meaningful step toward better glycemic control. Conclusion: A 12-week culturally tailored self-care education program involving patrilineal family members improved self-efficacy and glycemic control in T2DM patients. These findings highlight the importance of integrating local wisdom and family involvement into diabetes education to enhance patient empowerment and adherence.